Analis wypolnenija sakljutschitelnoi fasy pryschkow w wodu II i III klassa s platformy 10 metrow, lutschschich sportsmenow, na osnowe Olimpijskich igr w Tokio 2020 - Kurkin P. E. (Review of Pedagogical Research, 2024)
Abstract: in modern scientific papers, the information on kinematic characteristics of the most significant element of diving - water entry - is quite limited. There are publications by Gorokhovsky, Raspopova and other au thors, which consider the issues of splash formation during diving, but they do not fully cover theoretical and practical aspects of this sport. The question of the athletes' movement kinematics during diving, which provides a quality water entry, remains open. After obtaining the results of previous studies, it was decided to continue studying the technique of water entry after backward rotations. This paper considers II and III dives classes, from a 10-meter platform.